An innovative light-weight gravity installed plate anchor and its dynamic performance in clayey seabed. (15th October 2021) - Liu, Jun; Sun, Xingwei; Han, Congcong
Abstract: This paper presents a series of 1 g tests to investigate the performance of an innovative light-weight gravity installed plate anchor (L-GIPLA) with the aid of a reusable booster both in normally consolidated (NC) and lightly over-consolidated (LOC) soils. A micro-electromechanical systems (MEMS) accelerometer was used to measure the dynamic penetration process of the L-GIPLA with a booster in clay. Various factors affecting the final penetration depth of the anchor were investigated, including the soil strength characterisation, impact velocity, anchor shape, booster weight, and water entrainment effects. Based on the data obtained from the MEMS accelerometer, the hydrodynamic aspects associated with the water drag force and water entrainment effect during the dynamic penetration of the L-GIPLA were analysed. Besides, theoretical framework and energy-based models were proposed to predict the final penetration depth of the L-GIPLA. The excess pore water pressure induced by the dynamic penetration of the L-GIPLA and the subsequent dissipation around the anchor were investigated, hence the affected regions of the soil due to the dynamic penetration could be estimated. Finally, the penetration depth ratio and capacity-to-weight ratio of the proposed L-GIPLA were compared with that of other gravity installed anchors. Highlights: An innovative light-weight gravity installed plate anchor (L-GIPLA) is proposed. A relative high penetration depth ratio of the L-GIPLA is achieved by using a retrievable booster. The accumulation and dissipation of the excess pore pressure in the soil during and after dynamic installation are analysed.